ADVANCEMENTS IN RENEWABLE ENERGY TECHNOLOGIES AND THEIR IMPACT ON SUSTAINABLE DEVELOPMENT - Haydarov Hasanjon Hakimovich; Kushimov Bakhtiyor Alishovich (Journals Park Publishing, 2023)
This scientific article presents a comprehensive analysis of the advancements in renewable energy technologies and their impact on sustainable development. The study examines the key renewable energy sources, such as solar, wind, hydro, and geothermal, and evaluates their potential in addressing the global energy demand while mitigating climate change. The article also discusses the economic, social, and environmental benefits associated with the adoption of renewable energy technologies. A literature analysis is conducted to identify relevant studies, followed by a methodology section describing the research approach. The results highlight the significant progress made in renewable energy deployment, leading to reduced greenhouse gas emissions and improved energy access. The discussion delves into the challenges and opportunities for further advancement, emphasizing the importance of policy support and technological innovation [1]. The conclusion summarizes the key findings and proposes recommendations for policymakers, industry stakeholders, and researchers to accelerate the transition towards sustainable energy systems.
Keywords: Renewable energy, sustainable development, solar energy, wind energy, hydroelectric power, geothermal energy, climate change, energy access, policy support, technological innovation.